Mediating Effect of Organisational Culture between Leadership Values on Innovation: A Partial Least Squares (PLS) Path-Modeling - Mokhtar, Abdullah; Ab Hamid, Mohd Rashid; Zainol, Mustafa; Fazli, Idris; Nur Riza, Mohd Suradi (Universiti Teknologi Malaysia, 2013)
This exploratory study examined how leadership values affect innovation through organizational culture in organisations. A model of these relationships was created based on earlier research on value-based leadership and culture and a sample of 390 managers and personnel of Government-link companies in Malaysia. The model was assessed using Partial Least Squares (PLS) based Structural Equation Modeling (SEM). Analyses with the PLS technique confirmed all the hypotheses concerned. The results generally support significant relationships between leadership values, organisational culture and innovation. The study also confirmed the mediating role of organizational culture for the relationship between leadership values and innovation in organisations. The role of organizational culture is important for understanding how leadership values and innovation are related. The results of the study also suggest several aspects that may help organisations create conducive working environment supportive of innovation.